Átomos próximos à superfície: interação de van der Waals. E diodo laser acoplado à transição atômica: realimentação incoerente - Souza Segundo, Pedro Chaves de (2005)
Interactions with surfaces modify internal and external liberty degrees of atoms next to these surfaces. The dominant long range interaction (which extends itselfs to about an atomic transition wavelength is the van der Waals interaction, usually attractive. Firstly, this thesis treats C3 coefficient, which is characteristic of this interaction and depends on the type of surface and temperature. Other theme is determination of this coefficient using a spectroscopic technique (Selective Reflection) in the atomic cesium system (6S1=2 - 8P3=2 transition) on a dielectric surface. This interaction allows the long range excitation transfer (Förster effect) from atom to the dispersive dielectric surface. Considering small distances (atomic dimensions), interaction becomes repulsive because of electronic orbital overlap between the atom and surface components. The sum of these two kinds of interaction (far and close range) results in a potential well, with discrete energy levels. Next, are presented results of simulations on optic transfer from free atoms to atom-surface bounded states. The radiation sources used on the experiments to evidence atom-surface effects described in the first part of this thesis are resonant diode lasers, with spectral characteristics that must be modified on the laboratory to became useful tools to perform high resolution experiments. The Part II treats diode lasers, beginning from stabilization techniques description and going to a new technique developed on the laboratory during doctoral work, where the laser frequency is controlled by an coupled optical orthogonal feedback with atomic transition to diode. Other effects related to this stabilization technique, as the bi-stability phenomena, are described and interpreted on the last chapter.